Women work in Ancient Near East in the second and fi rst millennium B.C. - Ortega Balanza, Marta (Arenal. Revista de historia de las mujeres, 2009)
In addition to the housework (shopping, cooking, washing, knitting, sewing, raising children, or care for elder and sick people), women in Ancient Near East worked outside the home too, although this fact has been omitted or undervalued. Various sources show a wide range of trades and occupations, carried by both men and women, but laws regulate women’s work in only three occupations which are exclusively feminine: wet nurse and nursemaid, tavern keeper and prostitute. The article discusses what kind of jobs were performed by women in 1st and 2nd millennium BCE: agricultural worker, magician / healer, weaver, shopkeeper, hairdresser, midwife, etc., and why legislators were only interested in regulating the tavern keeping, the nursing and the prostitution.